RANCANG BANGUN APLIKASI SIMPAN DAN PINJAM PADA KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) WIJAYA MOJOKERTO - Setiawan, Hendra Prasetya Putra; Sulistiowati, Sulistiowati; Santoso, Rudi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract : Employees Cooperative Republic of Indonesia (KPRI) Wijaya Mojokerto is a container business that is engaged in savings and credit cooperatives. In the development of the cooperative Wijaya it turns out there are some problems caused by the management of transaction data, the difficulty to determine the loan and payment history data member who has paid or not paid. The problem potentially decreased in terms of performance or in terms of reporting on the cooperative Wijaya Mojokerto. So by knowing the problems that exist in cooperatives, savings and loan application implementation in cooperative Wijaya Mojokerto. Savings and loan application is capable of resolving the problems occurred as the management of transaction data, the difficulty to determine the loan and payment history data member who has paid or not paid off and improved performance on the process undertaken by the cooperative. Savings and loan applications can be used to manage and store data transactions made by the cooperative wijaya. This application can also generate reports such as reports of members, voluntary or compulsory savings report, report taking deposits, lending and payment reports reports.